Rewrite <math><mstyle displaystyle="true"><mn>100</mn></mstyle></math> as <math><mstyle displaystyle="true"><msup><mrow><mn>10</mn></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Since both terms are perfect squares, factor using the difference of squares formula, <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>-</mo><msup><mrow><mi>b</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>=</mo><mrow><mo>(</mo><mi>a</mi><mo>+</mo><mi>b</mi><mo>)</mo></mrow><mrow><mo>(</mo><mi>a</mi><mo>-</mo><mi>b</mi><mo>)</mo></mrow></mstyle></math> where <math><mstyle displaystyle="true"><mi>a</mi><mo>=</mo><mi>a</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>b</mi><mo>=</mo><mn>10</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>a</mi><mo>-</mo><mn>20</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>a</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>20</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>a</mi><mo>+</mo><mn>2</mn><mo>⋅</mo><mo>-</mo><mn>10</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mi>a</mi><mo>-</mo><mn>10</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>a</mi><mo>-</mo><mn>10</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mrow><mo>(</mo><mi>a</mi><mo>+</mo><mn>10</mn><mo>)</mo></mrow><mrow><mo>(</mo><mi>a</mi><mo>-</mo><mn>10</mn><mo>)</mo></mrow></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>a</mi><mo>-</mo><mn>10</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mrow><mo>(</mo><mi>a</mi><mo>-</mo><mn>10</mn><mo>)</mo></mrow></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>a</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>a</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mn>3</mn><mi>a</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>a</mi></mstyle></math> out of <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply <math><mstyle displaystyle="true"><mfrac><mrow><mi>a</mi><mo>+</mo><mn>10</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>a</mi></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Simplify the expression.

Multiply <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Reorder factors in <math><mstyle displaystyle="true"><mfrac><mrow><mrow><mo>(</mo><mi>a</mi><mo>+</mo><mn>10</mn><mo>)</mo></mrow><mi>a</mi></mrow><mrow><mn>6</mn></mrow></mfrac></mstyle></math> .

Do you know how to Simplify (a^2-100)/(3a)*(a^2)/(2a-20)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.